La nouvelle géopolitique des minéraux : Une étude sur l’évolution de l’impact international des minéraux stratégiques - Haglund, David (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
This article explores changes in the international political significance of "strategic minerals" over the past half-century. The method of analysis is comparative historical, or "diachronic", and the major issues examined are: 1) minerals as a cause of international conflict; 2) minerals as a factor contributing to the military potential of states; and 3) the question of mineral scarcity. In addition to the above issues, the author analyzes two central concepts, "geopolitics" and "strategic minerals" . He concludes that while it does make sense to speak of a "new geopolitics of Minerals" in the post-1973 era, there are nevertheless important ways in which recent strategic-minerals issues resemble those of the earlier period under examination, the interwar years (and, in particular, the 1930s). What does not seem to have changed in respect of strategic minerals since the 1930 s is that access to them continues ultimately to be a function of political processes, and therefore the access question remains what it was, a matter of geopolitical concern. Where there have been differences in the relevance of strategic minerals, these have mainly consisted in: 1) the declining importance of minerals as a major contributory factor in the breakdown of world order; 2) the lessening of what had formerly been a deterministic equation between mineral possession and military potential; and 3) the increased salience in the post-1973 era of the perception that access will be affected by the growing scarcity of minerals, whether due to the actual depletion of reserves or politically induced supply disruptions.